A DFT Computational and Synthetic Study of New Curcuminoidpropargyl Adducts with Pseudo‐Cofacial Aryl Rings. Issue 43 (14th November 2022) - Borosky, Gabriela L.; Laali, Kenneth K.
Abstract: With the aim to utilize transannular π‐π interactions as a driving force to assemble cofacial π‐decks, a DFT computational study was performed on the adducts resulting from coupling of curcuminoids (CURs), bearing electron‐withdrawing groups (F, CF3, SCF3, OCF3 ) in the aryl rings, with 1, 3‐diphenylpropargyl moiety and its p ‐OMe‐substituted derivatives. Detailed analysis of the structural and electronic properties of the resulting assemblies revealed the existence of intermolecular aromatic π‐π stacking interactions between one pair, and in some cases two pairs, of aryl rings. Structural/electronic changes resulting from π‐complexation to Ag + (mono and bis adducts), and to Cr(CO)3 acting as π‐electron sink, were also examined. Motivated by the DFT computations outcomes, the feasibility to access these adducts via a simple one‐pot reaction using bismuth nitrate as catalyst was shown in representative cases, along with complexation to AgOTf via an NMR study. Abstract : Presence of intermolecular aromatic π‐π stacking interactions in adducts resulting from coupling of curcuminoids bearing fluorinated substituents with 1, 3‐diphenyl‐propargyl moiety was demonstrated by DFT computations, and structural/electronic changes resulting from π‐complexation to Ag + and to Cr(CO)3 was also examined. Feasibility to synthesize these compounds by a simple one‐pot reaction is shown.